2018
DOI: 10.2116/analsci.18p302
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Porous Electrodes by the Anodization of Gold for an Application as Scaffolds in Direct-electron-transfer-type Bioelectrocatalysis

Abstract: In this study, nanostructured porous gold electrodes were prepared by the anodization of gold in the presence of oxalic acid or glucose as a reductant, and applied as scaffolds for direct electron transfer (DET)-type bioelectrocatalysis. Gold cations generated in the anodization seem to be reduced by the reductant to construct a porous gold structure. The DET-type performance of the electrode was examined using two DET-type model enzymes, bilirubin oxidase (BOD) and peroxidase (POD), for the four-electron redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…These reactions proceed in the following schemes in the simple case of the substrate's oxidation. On the other hand, we note here that some redox enzymes that have a catalytic site alone, without any other redox site(s), are also able to show DET-type bioelectrocatalysis, e.g., cytochrome c peroxidase [24], horseradish peroxidase (HRP) [25][26][27], ferredoxin-NADP + reductase [28], flavin adenine dinucleotide (FAD)-dependent glucose oxidase (FAD-GOD) [29,30], and FAD-dependent glucose dehydrogenase (FAD-GDH) [31]. Figure 1.…”
Section: Introductionmentioning
confidence: 92%
“…These reactions proceed in the following schemes in the simple case of the substrate's oxidation. On the other hand, we note here that some redox enzymes that have a catalytic site alone, without any other redox site(s), are also able to show DET-type bioelectrocatalysis, e.g., cytochrome c peroxidase [24], horseradish peroxidase (HRP) [25][26][27], ferredoxin-NADP + reductase [28], flavin adenine dinucleotide (FAD)-dependent glucose oxidase (FAD-GOD) [29,30], and FAD-dependent glucose dehydrogenase (FAD-GDH) [31]. Figure 1.…”
Section: Introductionmentioning
confidence: 92%
“…Recently, it was found that HRP showed a DET-type bioelectrocatalytic activity at mesoporous carbon and nanostructured gold electrodes [ 103 , 104 ] and third generation OP-type biosensors using the DET-type reaction of HRP were reported. Xia et al reported glucose and putrescine biosensors using GOD and putrescine oxidase, respectively [ 41 , 103 ].…”
Section: Multi-enzymatic Cascadesmentioning
confidence: 99%
“…Recently, it was found that HRP showed a DET-type bioelectrocatalytic activity at mesoporous carbon and nanostructured gold electrodes [103,104], and 3rd generation OP-type biosensors using the DET-type reaction of HRP were reported. Xia et al reported glucose and putrescine biosensors using GOD and putrescine oxidase, respectively [41,103].…”
Section: Peroxidase/oxidasesmentioning
confidence: 99%